Occurrence of Entamoeba gingivilis in patient with chronic periodtonitis (Mustansiria Dental Journal, 2005)
Recent studies have pointed the importance of Entamoeba gingivalis (E .gingivalis) as an active protozoa in periodontal pathology , its presence associated withthe presence of pathological pockets , thus a clinical survey of E, gingivalis wasconducted in patients with chronic periodontitis . A total of 240 specimens were takenHom 48 patients (20 male and 28 female) , their age ranged from 38 up to 60 years old .A direct smearing technique of deepest periodontal pocket (> 4mm) with a sterileuniversal curettes to pickup the plaque material and to be placed in phosphate — buffered `saline pl-{7.4, then stained with Heidenhair hematoxilyne modified technique, studiedunder light microscope , the results shown 33.3% of our patients were positive .The occurrence of E. gingivalis appeared positively correlated with the pocketdepth, 13.93% of 4-6mm pockets depth was positive, while in pockets of 7-8mm depththe percentage rises up to 38% .